DIFFERENCES IN THE PREVALENCE OF SYMPTOMS OF TEMPOROMANDIBULAR JOINT DISORDERS IN FACULTY OF DENTISTRY UNIVERSITAS JENDERAL ACHMAD YANI STUDENTS - Azkya Patria Nawawi; Isti Arifianti; Ryan Rhamdani Puspasanjaya (Journal of Health and Dental Sciences, 2023)
Temporomandibular joint disorder (TMD) is a common problem with various clinical signs and symptoms of the structures of the masticatory system, including the masticatory muscles and the temporomandibular joint, often found in the age group of 20-40 years. People with TMD symptoms can show at least one symptom of the disorder. The prevalence of TMD was reported among dental students. This study aims to determine differences in the majority of symptoms of temporomandibular joint disorder in students of the Faculty of Dentistry, Jenderal Achmad Yani University class of 2020 in 2021 and 2023. This research is an analytical study using a cross-sectional approach. Data were analyzed using the Wilcoxon signed-rank test with 54 research subjects from the Faculty of Medicine class 2020. This study found that in 2021, there were 88.8% of students, while in 2023, 87% of students suffered from symptoms of temporomandibular joint disorder with a score p=0.739. No significant difference in the prevalence of temporomandibular joint disorder symptoms in 2021 and 2023. DOI : 10.54052/jhds.v3n2.p157-168